A Comparison of the Variable Sampling Interval (VSI) and Variable Sample Size (VSS) Coefficient of Variation Charts - Lim, Sok Li; Yeong, Wai Chung; Michael Khoo, Boon Chong; Chew, Xin Ying (2018)
An efficient way to perform quality monitoring is important for a lot of industries, particularly in the manufacturing industry. Control charts are one of the important tools to monitor quality. Recently, control charts monitoring the coefficient of variation (CV) are proposed to monitor processes which do not have a constant mean and a standard deviation which changes with the mean. These processes cannot be monitored by standard control charts which monitor the mean and/or standard deviation. The Variable Sampling Interval (VSI) and Variable Sample Size (VSS) CV charts are two recent charts proposed to improve the detection ability of CV charts. This paper compares the performance between these two charts in terms of the Average Time to Signal (ATS). The comparison shows that the VSS CV chart shows better performance when either a small sample size is taken or when a small shift in the CV needs to be detected. Alternatively, the VSI CV chart outperforms the VSS CV chart. This paper will enable practitioners to know the conditions where the VSS CV chart outperforms the VSI CV chart, and vice versa. Hence, practitioners will be able to decide whether it is better to monitor their processes with a VSI or VSS scheme.